Pengaruh Penataan Lingkungan Belajar Terhadap Hasil Belajar Anak Usia 5-6 Tahun di Tk Beringin Permai Kecamatan Sipoholon (Jurnal Pendidikan Agama dan Teologi, 2023)
Optimizing the arrangement of the classroom learning environment will be the key to achieving learning objectives so that a meaningful learning pattern is achieved. Building a classroom environment is meant as effective classroom management to support learning, or also known as creating a conducive learning atmosphere. Structuring the classroom environment is defined as the process of coordinating and integrating all sources, both human, facilities and other technical resources to achieve certain goals that have been set. Keywords: structuring the learning environment, learning outcomes, Early Childhood